Were There Regime Switches in U.S. Monetary Policy? - Sims, Christopher A; Zha, Tao (American Economic Review, 2006)
A multivariate regime-switching model for monetary policy is confronted with U.S. data. The best fit allows time variation in disturbance variances only. With coefficients allowed to change, the best fit is with change only in the monetary policy rule and there are three estimated regimes corresponding roughly to periods when most observers believe that monetary policy actually differed. But the differences among regimes are not large enough to account for the rise, then decline, in inflation of the 1970s and 1980s. Our estimates imply monetary targeting was central in the early 1980s, but also important sporadically in the 1970s.